HUBUNGAN STRES DENGAN GANGGUAN SIKLUS MENSTRUASI SANTRIWATI DISEBUAH ISLAMIC BOARDING SCHOOL - Utami, Anisa Fara (NURSE: Journal of Nursing and Health Science, 2024)
Background: Around 11.7% of Indonesian adolescent girls experience irregular menstrual cycles. This can occur, among others, due to stress. Teenage students in boarding schools experience stress due to more stressors than general students, such as the difficulty of adapting to the environment and the density of activities while living. Stress can affect the menstrual cycle because it can interfere with the production of estrogen and progesterone. The purpose was conducted to determine the relationship between stress and menstrual cycle disorders in students of class X in Pesantren. Method: This study used a quantitative correlative analytic design with a cross sectional approach through a primary data survey. Data were generated from the distribution of the PSS-10 questionnaire and the menstrual cycle disorder questionnaire. The population and sample were 96 students and the sample was determined using total sampling. Results: The results showed that 16 (24.6%) experienced severe stress, 44 (67.7%) experienced moderate stress, and 5 (41.9%) experienced mild stress accompanied by menstrual cycle disorders. Conclusion: Data analysis using correlation test showed that stress was associated with menstrual cycle disorders with a value of p=0.000 (α = 5%). Therefore, it is recommended that the collaborate to conduct screening and provide information related to stress and menstruation to santri